Effects of Women's Perception in their Buying Behavior along Fairview Quezon City: Vol.3, No.1A (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
We cannot deny how fashionable women are. They can change the trends by simply changing the fashions every time. Problems like unexpected changes in decisions, not having enough finances, and acting differently on what is a must are the things that should be observed, and issues like the perception of women can change their decisions and why there is a lack of studies about this side of the business industry. This study can provide solid information and enlightenment to other past related research that can help them solidify their papers. This survey research was conducted to determine the Effects of women's perception on their buying behaviour along Fairview Quezon City. This study utilizes a qualitative research design method and a simple random technique as a sampling technique. The instrument used in the study is an online questionnaire distributed among 50 random women in Fairview, Quezon City, with the following statistical tools: frequency, percentage, and weighted mean.Most guests visiting Along Fairview Quezon City were 17-50 years old. Old. The survey result showed that 19 – 25-year-olds dominate with 45 respondents or 90%, Non-working dominates with 36 respondents or 72%, Single dominates with 39 respondents or 78%, and None – 10,000 dominates with 38 respondents or 76%. The Overall composite mean of Product, Price, Place, and Promotion is 3.42, interpreted as Agree. The overall composite mean of decision-making, financial status, trends, and needs is 3.20, interpreted as agreeable. Most respondents chose the unexpected change of mind (72%) as a challenge in their buying behaviour, followed by out-of-reach prices (50%) and the rest.This study's result would benefit companies, students, and researchers who want to study the benefits of women's perception in their buying behaviour. It will inform the audience about the significant and minor problems women can face in their buying behaviour and will also guide them to enhance and resolve those problems.
Keywords: Women Perception; Buying Behavior; Unexpected Change of Mind